Assessment of Language and Literacy in Children Who Are d/Deaf and Hard of Hearing - Lianna Pizzo; Amanda Chilvers (MDPI AG, 2019)
This article presents theoretical orientations and practical applications for the assessment of d/Deaf and hard of hearing (d/Dhh) children. It discusses current approaches to assessment and the factors affecting d/Dhh children’s participation in assessments using those approaches. Gaps in the field around access to appropriate assessments are discussed. This review also shares information on the relationship between the purpose of the assessment and the approach selected. Basic considerations for both d/Deaf and hard of hearing multilingual learners (d/DMLs) and d/Dhh children with additional disabilities will be addressed. Finally, general recommendations are made for research and practice.